Oxidative stress in the liver of chicken during fowl adenovirus serotype 4 infection - Jiayu Sun; Xu Cao; Yufeng Li; Kexiang Yu; Yanfang Cong; Qing Pan; Yanbo Yin; Jianlin Wang (Poultry Science)
Hepatitis is a significant pathological manifestation of fowl adenovirus serotype-4 (FAdV-4) infection, which is a crucial factor contributing to the mortality of chickens. The pathophysiology of liver disease is rooted in oxidative stress. The present study aims to investigate the presence of oxidative stress during the liver lesion process in FAdV-4 infection. Specifically, one-day-old specific pathogen-free (SPF) chickens were allocated into three groups, the control group, the infection group, and the quercetin group. The quercetin group received daily oral administration of quercetin. At the age of 12 days, the chickens belonging to both the infection and quercetin groups were subjected to intramuscular injection of FAdV-4 (0.3 mL103TCID50/mL). Samples were collected from each group at 2, 4, and 6 days post-infection (dpi), and sera were collected to measure the levels of ALT and AST. A portion of liver tissue was fixed to examine the histological changes, cell apoptosis, and mitochondrial morphology, while another portion was homogenized and mitochondria were isolated. The levels of MDA, SOD, H2O2, and GSH-Px in the homogenate supernatants of livers and isolated mitochondria were measured, and the viral load in the liver was studied. And Cyt C levels in the mitochondria and cytosolic supernatant were recorded. The results showed that AST and ALT in the serum of chicken in the infection group were significantly higher than those in the control and quercetin group at 6 dpi. Obvious swelling, steatosis, necrosis, and inflammatory cell infiltration were observed in the liver of the infection group. Administered with quercetin can significantly decrease the viral load in the liver at 4 and 6 dpi. H2O2 in the liver, and MDA, H2O2, GSH and SOD levels in mitochondria in the hepatocyte of the infection group were significantly higher than those in the control and quercetin groups. Cyt C in the mitochondria of the hepatocyte of infection and quercetin groups were significantly lower than those in the control group at 2 dpi. Cyt C in the cytoplasm of the liver in chicken in the quercetin group was significantly higher than those in the control and infection groups. It was found that the outer mitochondrial membrane in hepatocytes was fractured in the infection group. The proportion of apoptotic cells in the liver in the infection groups was significantly higher than those in the control and quercetin group at 4 dpi, and that in the control group was significantly lower than in the infection and quercetin group. The results suggested that during liver injury induced by FAdV-4 infection, oxidative damage occurred obviously in the liver and mitochondria, and hepatocyte apoptosis was observed. Quercetin, as an antioxidant, can inhibit virus replication to some extent, and alleviate oxidative damage, liver damage, and the mortality caused by FAdV-4 infection.